1970
DOI: 10.1126/science.167.3916.297
|View full text |Cite
|
Sign up to set email alerts
|

"Antidotal Thirst": A Response to Intoxication

Abstract: Albino rats increased their intake of water soon after they were given a load of 0.12 molar lithium chloride in the stomach. Alterations in blood volume and tonicity could not account for the magnitude of the thirst observed, which served to facilitate the renal excretion of the toxic lithium ions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
1

Year Published

1971
1971
1989
1989

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 6 publications
2
10
1
Order By: Relevance
“…It was recently suggested that lithium polyuria in the rat resulted from excessive intake of water (34). The present experiments exclude this explanation.…”
supporting
confidence: 49%
“…It was recently suggested that lithium polyuria in the rat resulted from excessive intake of water (34). The present experiments exclude this explanation.…”
supporting
confidence: 49%
“…Rather, Li may act directly upon thirst mechanisms (Smith & Balagura, 1972), so that the polyuria is secondary (Smith, Balagura & Lubrau, 1970). Thus in the DI rat, Li produces a primary polydipsia, while in LE rats polyuria may be induced perhaps in combination with a central neural action on water intake.…”
Section: Discussionmentioning
confidence: 99%
“…Lithium causes polydipsia which may act to increase renal activity and thus lithium excretion (Smith et al, 1970). Alternatively, when water was not present the rats learned to avoid both bottles, whereas when water was available in one bottle this increased the probability of sampling the wrong bottle (i.e., lithium) since these were switched over each day.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have used either water (Smith et al, 1970) or saline (Thomsen et al, 1974) for the investigation of lithium toxicity. The present work supports the view that both liquids act, presumably, to reduce the retention of lithium ions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation